Verbascum mughlaeum (Scrophulariaceae), a new species from SW Anatolia, Turkey - Duman, Hayri̇; Uzunhi̇sarcikli, M. Erkan; Tan, Kit (Phytotaxa, 2017)
Verbascum mughlaeum (Scrophulariaceae) is described as a species new to science and illustrated. It is a local endemic restricted to the provinces of Muğla and Antalya in SW Anatolia, Turkey. There are some morphological similarities with V. syriacum, endemic to the E Aegean island of Rhodos (Greece) and its affinities with this species is discussed.